A systematic review and meta‐analysis of thiazide‐induced hyponatraemia: time to reconsider electrolyte monitoring regimens after thiazide initiation?. (April 2015) - Barber, Jennifer; McKeever, Tricia M.; McDowell, Sarah E.; Clayton, Jennifer A.; Ferner, Robin E.; Gordon, Richard D.; Stowasser, Michael; O'Shaughnessy, Kevin M.; Hall, Ian P.; Glover, Mark
Abstract : Aims: Hyponatraemia is one of the major adverse effects of thiazide and thiazide‐like diuretics and the leading cause of drug‐induced hyponatraemia requiring hospital admission. We sought to review and analyze all published cases of this important condition. Methods: Ovid Medline, Embase, Web of Science and PubMed electronic databases were searched to identify all relevant articles published before October 2013. A proportions meta‐analysis was undertaken. Results: One hundred and two articles were identified of which 49 were single patient case reports. Meta‐analysis showed that mean age was 75 (95% CI 73, 77) years, 79% were women (95% CI 74, 82) and mean body mass index was 25 (95% CI 20, 30) kg m −2 . Presentation with thiazide‐induced hyponatraemia occurred a mean of 19 (95% CI 8, 30) days after starting treatment, with mean trough serum sodium concentration of 116 (95% CI 113, 120) mm and serum potassium of 3.3 (95% CI 3.0, 3.5) mm . Mean urinary sodium concentration was 64 mm (95% CI 47, 81). The most frequently reported drugs were hydrochlorothiazide, indapamide and bendroflumethiazide. Conclusions: Patients with thiazide‐induced hyponatraemia were characterized by advanced age, female gender, inappropriate saliuresis and mild hypokalaemia. Low BMI was not found to be a significant risk factor, despite previous suggestions. The time from thiazide initiation to presentation with hyponatraemia suggests that the recommended practice of performing a single investigation of serum biochemistry 7–14 days after thiazide initiation may be insufficient or suboptimal. Further larger and more systematic studies of thiazide‐induced hyponatraemia are required.